1981
DOI: 10.1111/1523-1747.ep12525784
|View full text |Cite
|
Sign up to set email alerts
|

Skin Calcium Binding Protein is Localized in the Cytoplasm of the Basal Layer of the Epidermis

Abstract: Using a serum raised in rabbits against a calcium binding protein extracted from rat skin, the cutaneous localization of this protein was studied by indirect immunofluorescence. The skin calcium binding immunoreactivity was found in the epidermis but not in the dermis; it was localized in the cytoplasm of the basal cell layer of both skin and malpighian mucosa. There was not species specificity; this allowed the tracing of the protein in human epidermis as well where it was also expressed only in the basal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Neither the FITC labelled sheep anti-rabbit IgG antiserum nor the FITC labelled goat ami-human IgG antiserum reacted with normal skin or tumorous material. Previous absorption of SCaBP antiserum with purified SCaBP abolished the staining as detailed previously (Saurat et al, 1981a). No staining was observed with pre-immune serum.…”
Section: Controlssupporting
confidence: 53%
See 1 more Smart Citation
“…Neither the FITC labelled sheep anti-rabbit IgG antiserum nor the FITC labelled goat ami-human IgG antiserum reacted with normal skin or tumorous material. Previous absorption of SCaBP antiserum with purified SCaBP abolished the staining as detailed previously (Saurat et al, 1981a). No staining was observed with pre-immune serum.…”
Section: Controlssupporting
confidence: 53%
“…A rabbit serum containing antibodies against purified rat SCaBP was obtained as previously described (Laouri et al., 1980;Saurat et al, 1981a). Briefly, SCaBP from whole Sprangley albino rat skin was extracted by homogenization, and purified by chromatography.…”
Section: Antiserummentioning
confidence: 99%
“…3 Skin calciumbinding protein immunoreactivity has also been localized to the cytoplasm of basal epidermal cells in humans. 4 In the study of Merot et al, 5 skin calcium-binding protein immunoreactivity was demonstrated in all human basal cell carcinoma cells regardless of histologic type or position of cells in relation to the basement membrane. The only squamous cell carcinoma examined showed skin calcium-binding protein immunoreactivity in only a few cells confined to the periphery of the tumor.…”
Section: Discussionmentioning
confidence: 94%
“…c) Serum to skin calcium-binding protein (SCaBP): this serum was raised in rabbit to a skin protein (mol.wt. 12,000) with calcium-binding activity [q which is expressed in the cytoplasm of epidermal basal cells [14]; the serum reacted identically with basal cells of orthokeratotic, parakeratotic, and mucous epithelia. The titre was 1 :640, the working dilution 1 /20.…”
Section: Other Seramentioning
confidence: 95%